2012
DOI: 10.1007/s11357-012-9421-y
|View full text |Cite
|
Sign up to set email alerts
|

Aging might augment reactive oxygen species (ROS) formation and affect reactive nitrogen species (RNS) level after myocardial ischemia/reperfusion in both humans and rats

Abstract: Previous studies indicate aging results in significantly decreased cardiac function and increased myocardial apoptosis after myocardial ischemia/reperfusion (MI/R) in humans or rats. The underlying mechanisms of aging-exacerbated effects remain unknown. Reactive oxygen species (ROS) and reactive nitrogen species (RNS) are known to play vital roles in aging-related MI/R injury. Heretofore, the effects of aging upon ROS and RNS formation were not investigated in humans, which is the focus of the current study. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 15 publications
4
43
0
1
Order By: Relevance
“…This lack of studies in middle-aged is striking, since an ischemic episode in patients begins at that stage of life, and they are not exclusive of advanced age [90,91]. However, it is known that even though oxidation processes start when life begins; it is in middle-aged that they reach sufficient levels to trigger deleterious mechanisms on different cell components [92], and this ROS increase is able to modify expression and/or activity of several proteins [93][94][95]. In a recent paper from our lab, we showed that young mice overexpressing Trx-1 have a smaller infarct size compared to their corresponding Wt mice [96].…”
Section: Thioredoxin In Aging Heartsmentioning
confidence: 99%
“…This lack of studies in middle-aged is striking, since an ischemic episode in patients begins at that stage of life, and they are not exclusive of advanced age [90,91]. However, it is known that even though oxidation processes start when life begins; it is in middle-aged that they reach sufficient levels to trigger deleterious mechanisms on different cell components [92], and this ROS increase is able to modify expression and/or activity of several proteins [93][94][95]. In a recent paper from our lab, we showed that young mice overexpressing Trx-1 have a smaller infarct size compared to their corresponding Wt mice [96].…”
Section: Thioredoxin In Aging Heartsmentioning
confidence: 99%
“…In aging hearts, high levels of nitric oxide (NO) are converted to a number of more reactive derivatives, known collectively as reactive nitrogen species (RNS). 6 Peroxynitrite (ONOO -), an extremely important RNS, is a highly reactive species and oxidizes or nitrates (e.g., tyrosine nitration) a variety of molecules, and this has been shown to induce cardiomyocyte death. 7 The glutathione (GSH) anti-oxidant system has been demonstrated to be a defense against ONOO -.…”
Section: Introductionmentioning
confidence: 99%
“…рис.2,б). Окисний (як оксидативний, так і, особливо, нітрозативний) стрес, який спо-стерігається за умов старіння [2], є його першопричиною [18], і також мішенню дії препарату. На це вказує зафіксоване знижен-ня генерації *О 2 -в еритроцитах і пулів Н 2 О 2 як в еритроцитах, так і в плазмі (див.…”
Section: показникunclassified